The impact of smartphone use on student learning experience in higher education in South Africa - Toperesu, B-Abee (Department of Information Systems, 2021)
Background: The use of mobile devices for learning has been on the increase due to the availability of affordable data and free WiFi networks across institutions of higher learning. However, very few studies seek to understand if there is any impact that these devices have on a student's overall learning experience particularly from a developing country's perspective. Objectives: This research study determines the positive and negative impacts smartphone use has on a student's learning experience and whether this leads to overall satisfaction with mobile learning. Methods/Approach: Quantitative and qualitative data were collected through an online survey that was distributed via email to a student body from the sample. Statistica software was used to analyse the quantitative data while Nvivo software was used to analyse the qualitative data. Results: With over 400 responses, we found evidence for some, but not all hypothesized positive and negative impacts. Additionally, there was very strong support for how these impacts contribute to the overall satisfaction of using a smartphone for learning, explaining more than 60% of the variance. Conclusions: We found that the overall positive satisfaction leads to differentiated, continued uses of the smartphone for learning.